Exploring Informal Caregivers’ Perspectives on Oral Care for Stroke Patients - Rani, Haslina; Zamzuri, Saidatul Najibah Muhammad; Omar, Ezzah; Mohd-Dom, Tuti Ningseh; Abdul Aziz, Aznida Firzah; Ali, Mohd Fairuz (UI Scholars Hub, 2024)
Stroke often results in physical disability and functional impairment, which may severely limit patients' ability to care for personal hygiene, including oral care. This study aimed to identify the challenges faced by informal caregivers in managing the oral health of stroke patients. This study conducted semi-structured individual interviews with eight home-based caregivers of stroke patients recruited from a community-based clinic facility of a public university in Malaysia. The interviews took 30-45 minutes to complete and were transcribed verbatim. Transcripts were analyzed thematically using a phenomenological approach. Relevant themes that emerged were variations in oral hygiene care, caregivers’ concerns in providing oral care, dental clinic utilization, and caregivers’ perceived educational and training needs. This study highlights the challenges faced by caregivers in managing the oral health of stroke patients. Improving access to dental services for stroke patients and tailoring educational programs to suit the specific learning needs of caregivers, as identified in this study, may result in improved health outcomes for stroke patients.